2020
DOI: 10.46690/ager.2020.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Decline curve analysis for multiple-fractured horizontal wells in tight oil reservoirs

Abstract: The production of multiple-fractured horizontal wells (MFHW) in tight oil reservoirs decreases rapidly in the initial period. It then enters a stable state of the low production with a slow loss-ratio. Because of its complicated production dynamic characteristics, the conventional rate-decline analysis method is no longer applicable. We adopt the semianalytical solution of the MFHW five-region linear flow model to get the multiple-fractured dimensionless rate-decline analysis curves and continuously calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…www.nature.com/scientificreports/ Water invasion analysis. Currently, the main methods of water invasion degree identification can be divided into three main methods: the pressure drop curve method, the apparent geological reserves method and the water invasion volume coefficient method [30][31][32][33] . Using the water invasion volume coefficient method, the θ ∼ R curves of Group I were drawn; details are presented in Appendix A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ Water invasion analysis. Currently, the main methods of water invasion degree identification can be divided into three main methods: the pressure drop curve method, the apparent geological reserves method and the water invasion volume coefficient method [30][31][32][33] . Using the water invasion volume coefficient method, the θ ∼ R curves of Group I were drawn; details are presented in Appendix A.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the main methods of water invasion degree identification can be divided into three main methods: the pressure drop curve method, the apparent geological reserves method and the water invasion volume coefficient method 30 – 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the main methods of water invasion degree identification can be divided into three main methods: the pressure drop curve method, the apparent geological reserves method and the water invasion volume coefficient method (Chen 1978; Abdul-Majeed and Al-Assal 1998; Siddiqui et al 2010;Xu et al 2020).…”
Section: Water Invasion Analysismentioning
confidence: 99%
“…Previous studies have shown that the influence of fracture geometrical parameters, in particular the fracture scale, is substantial with respect to effective permeability and rock physical properties (de Dreuzy et al ., 2001; Tran et al ., 2006; Wang et al ., 2017; Ghasemi et al ., 2020). During reservoir production and shale gas fracturing, the effective hydraulic fracturing treatment is necessarily influenced by the distribution and geometry of the natural fracture system as well as by the present maximum horizontal stress (Gale et al ., 2007; Zhang et al ., 2019; Xu et al ., 2020). The injected hydrate raises the fluid pressure, which creates new fractures and causes the growth of existing fractures, thus providing improved permeability and enhancing the hydraulic fracturing treatment and reservoir production (Liu et al ,.…”
Section: Introductionmentioning
confidence: 99%